2009
DOI: 10.1083/jcb.200808016
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin SMC1β protects telomeres in meiocytes

Abstract: Telomeres fail to attach to the nuclear envelope and lose structural integrity in cells lacking SMC1β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 50 publications
11
120
1
2
Order By: Relevance
“…Thus, we speculate that at least two non-mutually exclusive events might lead to the appearance of internal telomeres in the absence of CDK2. The first one implies that some telomeres are unable to attach to the nuclear envelope during leptotene, and therefore remain in the nucleoplasm in further prophase I stages, as described in knockout mouse models for Smc1b 2/2 and Sun1 2/2 mice (Adelfalk et al, 2009;Ding et al, 2007). An alternative, and more fascinating possibility, consists in the detachment of telomeres that were initially attached to the nuclear envelope, accounting for the increase in the rate of non-attached telomeres in zygotene and pachytene-like nuclei.…”
Section: Cdk2 Mediates Meiotic Telomere Attachment and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we speculate that at least two non-mutually exclusive events might lead to the appearance of internal telomeres in the absence of CDK2. The first one implies that some telomeres are unable to attach to the nuclear envelope during leptotene, and therefore remain in the nucleoplasm in further prophase I stages, as described in knockout mouse models for Smc1b 2/2 and Sun1 2/2 mice (Adelfalk et al, 2009;Ding et al, 2007). An alternative, and more fascinating possibility, consists in the detachment of telomeres that were initially attached to the nuclear envelope, accounting for the increase in the rate of non-attached telomeres in zygotene and pachytene-like nuclei.…”
Section: Cdk2 Mediates Meiotic Telomere Attachment and Dynamicsmentioning
confidence: 99%
“…Indeed, the fact that the number of internal SUN1 foci increased during prophase I progression, as synapsis proceeds, also reinforces this proposal. In this context, it has been shown that SUN1 persists at the axial and lateral elements ends on spread spermatocytes after a harsh preparative technique that disrupts the nuclear envelope (Adelfalk et al, 2009;Ding et al, 2007;Morimoto et al, 2012). Accordingly, SUN1 at detached telomeres in Cdk2 2/2 spermatocytes could bring with them vesicles derived from the nuclear envelope.…”
Section: Cdk2 Mediates Meiotic Telomere Attachment and Dynamicsmentioning
confidence: 99%
“…The absence of this protein leads to defects in chromosome synapsis, recombination, and meiotic progression in mammals (Ding et al 2007;Link et al 2014). We investigated the location of SUN1 protein using an antibody against mouse SUN1 (Adelfalk et al 2009). We found that SUN1 localized at the telomeres of meiotic bivalents in the Mongolian gerbil ( Figure 7A) as a single or double spot at the end of the SC.…”
Section: Association Of Centromeric Regions With the Nuclear Envelopementioning
confidence: 99%
“…The identity of each population was confirmed by assessing the type of SCP3 immunofluorescence on chromosomes of sorted cells from each subset. To confirm that cell populations, which by Hoechst staining appeared as 4N are indeed spermatocytes, we crossed the Rad9a f/del Cre + line to transgenic mice expressing EGFP under the meiosis-specific Smc1b promoter described previously (Adelfalk et al, 2009). In this mouse line EGFP expression starts at the onset of prophase I.…”
Section: Immunofluorescencementioning
confidence: 99%